Translation and Validation of the Readiness to Change Questionnaire for Alcohol Drinkers into an Indigenous Language (Jakun Version) in Malaysia - Rasuli, Rifhan; Mohamad, Mariam; Mat Ruzlin, Aimi Nadira (IIUM Medical Journal Malaysia, 2026)
INTRODUCTION: Assessing readiness to change is crucial in managing alcohol-related conditions and can be achieved by using the Readiness to Change Questionnaire (RCQ), grounded in the Transtheoretical Model (TTM). This is especially important in Indigenous communities in Peninsular Malaysia, where alcohol use is intertwined with cultural practices. This study aimed to translate and validate the RCQ from English into the Jakun language spoken by an Indigenous tribe in Malaysia to ensure its linguistic and cultural relevance for assessing readiness to change among Jakun alcohol drinkers. MATERIALS AND METHODS: This cross-sectional study was conducted among current alcohol drinkers in three Indigenous Jakun settlements in Rompin, Pahang, Malaysia. The RCQ underwent translation into Jakun language, followed by validation (face and construct) and reliability assessment. Exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and internal consistency were used to evaluate its construct validity and reliability. RESULTS: A total of 317 participants were recruited, most of whom were males, aged 18-29, married, had primary education, were self-employed, and had low household income. From the EFA, the original three factors were retained (pre-contemplation, contemplation, and action), but three items were removed, one from each construct. The final model demonstrated acceptable fit in CFA. Cronbach’s alpha values ranged between 0.733 and 0.838, indicating good internal consistency. CONCLUSION: The RCQ (Jakun version) is a valid and reliable tool for assessing readiness to change among Indigenous Jakun alcohol drinkers. It can potentially assist healthcare professionals in tailoring interventions based on stages of change to address risky alcohol use in this population.